2017
DOI: 10.1080/07347332.2017.1329769
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of partners of prostate cancer survivors: A qualitative study

Abstract: Prostate cancer, Australia's leading cancer, has treatment side effects that reduce the quality of life for both survivors and partners. Limited partner research exists. This study aimed to address this gap in the literature by gathering data directly from partners to obtain a deeper understanding of their experiences of prostate cancer survivorship that helps inform healthcare service providers. A qualitative approach was taken to explore participant views (N = 16) through three focus groups and two in-depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(52 citation statements)
references
References 31 publications
0
52
0
Order By: Relevance
“…When compared with some previous related studies among Caucasian [7] and African American [9] populations, it appears that the implications of CaP may be more complicated for partners within BA and BC populations due to complex socio-cultural influences. This suggests the Bearing in mind the centrality of their husband's recovery and wellbeing to the women's lives, there is further need for holistic interventions delivered in a culturally sensitive manner to address the influence of CaP on the sexual health and mental well-being of men and partners both as individuals and as a couple [22].…”
Section: Implications For Practicementioning
confidence: 74%
See 2 more Smart Citations
“…When compared with some previous related studies among Caucasian [7] and African American [9] populations, it appears that the implications of CaP may be more complicated for partners within BA and BC populations due to complex socio-cultural influences. This suggests the Bearing in mind the centrality of their husband's recovery and wellbeing to the women's lives, there is further need for holistic interventions delivered in a culturally sensitive manner to address the influence of CaP on the sexual health and mental well-being of men and partners both as individuals and as a couple [22].…”
Section: Implications For Practicementioning
confidence: 74%
“…Findings from this study suggested that the BA/BC cultural marital context uniquely influenced participants' experiences as they traversed the CaP journey. Unlike a related study involving Caucasian participants [7] where partners were very much involved in their men's health, Reiterating cultural expectations for the man to be the head of the family who leads in core areas such as decision-making, sex and bread-winning [19,20], our study participants recognised how these influenced their husbands' behaviour towards their CaP and expectations of their partners.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…NNSRP can cause psychological and emotional alterations that compromise the patient’s adaptation to the new situation (Lehto et al, 2017), which can affect their immediate environment, particularly their partner (Paterson et al, 2015). Other studies suggest that these emotional conflicts after NNSRP can culminate in an inability to maintain satisfactory intimate relationships (Chambers et al, 2013; Pinks et al, 2018). These sexual issues can cause negative feelings in the recovery phase (Lambert et al, 2016) that affect relationship satisfaction (Manne et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Despite sexuality being one of the main unmet demands that concerns patients (Pinks et al, 2018), healthcare professionals (formal structural social support) usually overlook it during treatment (Cousseau et al, 2016; Granero-Molina et al, 2018). Management behaviors for psychological and physical problems (Paterson et al, 2014), as well as decision-making (Laidsaar-Powell et al, 2016) in patients with prostate cancer have been researched.…”
mentioning
confidence: 99%